2017
DOI: 10.3390/catal7030093
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Water Oxidation on ZnO: A Review

Abstract: Abstract:The investigation of the water oxidation mechanism on photocatalytic semiconductor surfaces has gained much attention for its potential to unlock the technological limitations of producing H 2 from carbon-free sources, i.e., H 2 O. This review seeks to highlight the available scientific and fundamental understanding towards the water oxidation mechanism on ZnO surfaces, as well as present a summary on the modification strategies carried out to increase the photocatalytic response of ZnO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(65 citation statements)
references
References 106 publications
0
57
0
Order By: Relevance
“…Degradation and demineralization results of TiO 2 catalystbased experiments were better as compared to those with ZnO catalyst. ZnO catalyst has potential to achieve improved photocatalytic performance as it absorbs over an appreciable region of the UV-Vis spectrum (Hamid, The, & Lai, 2017). But it is more susceptible to photo corrosion as compared to TiO 2 , shows less charge separation efficiency and it has poor light absorbance for solar irradiation (Kong, Zhai, Wang, Zhao, & Li, 2017).…”
Section: Short Communicationmentioning
confidence: 99%
“…Degradation and demineralization results of TiO 2 catalystbased experiments were better as compared to those with ZnO catalyst. ZnO catalyst has potential to achieve improved photocatalytic performance as it absorbs over an appreciable region of the UV-Vis spectrum (Hamid, The, & Lai, 2017). But it is more susceptible to photo corrosion as compared to TiO 2 , shows less charge separation efficiency and it has poor light absorbance for solar irradiation (Kong, Zhai, Wang, Zhao, & Li, 2017).…”
Section: Short Communicationmentioning
confidence: 99%
“…Only a few reports relate to nanomaterials [12][13][14] and most often than not, the photocatalytic material is TiO 2 [15][16][17][18] . ZnO is an interesting alternative to TiO 2 , many research groups all over the world focused on this promising research field: developments of ZnO-based photocatalyst in water treatment technology [19][20][21][22][23][24][25][26] . In a recent report of our group, ZnO NWs were proven to be efficient photocatalyst 27 .…”
Section: Introductionmentioning
confidence: 99%
“…The negatively charged CO 2 reduction intermediates will more preferably bound to the terminal sites that are slightly positively charged and thus will increase the activity and selectivity of CO 2 reduction reaction. It has been reported that ZnO with exposed site [0001] has terminal Zn atom that is slightly positively charged and hence has higher photocatalytic activity for water splitting [199]. As such, it was postulated that preferential crystal growth leading to a high degree of exposure of the [0001] facets would enhance its catalytic activity.…”
mentioning
confidence: 99%
“…nanowires, nanorods, core/shell, nanoflowers and nanobelts etc. are reported in literature [199][200][201][202][203][204][205][206][207][208][209][210][211][212]. The role of morphology beside balancing the light absorption depth and controlling the charge carrier diffusion length is of utmost important as it varies the type and amount of exposed crystal facets.…”
mentioning
confidence: 99%
See 1 more Smart Citation